2018
DOI: 10.1016/j.omtm.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Reactivating and Expanding T Cells Specific for Rhizopus oryzae

Abstract: Mucormycosis is responsible for an increasing proportion of deaths after allogeneic bone marrow transplantation. Because this disease is associated with severe immunodeficiency and has shown resistance to even the newest antifungal agents, we determined the feasibility of reactivating and expanding Rhizopus oryzae-specific T cells for use as adoptive immunotherapy in transplant recipients. R. oryzae extract-pulsed monocytes were used to stimulate peripheral blood mononuclear cells from healthy donors, in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…In this cohort, 26 patients underwent two or more debridement procedures or extended surgical resections (range 2–14), some with considerable long‐term sequelae. Recent studies have raised hopes for innovative alternative treatment strategies for mucormycosis (Armstrong‐James et al , ; Castillo et al , ) Currently, surgical debridement is strongly recommended for rhinocerebral and soft‐tissue mucormycosis according to the ECIL‐6 guidelines and it is advised for case‐by‐case consideration for pulmonary and disseminated mucormycosis (Tissot et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, 26 patients underwent two or more debridement procedures or extended surgical resections (range 2–14), some with considerable long‐term sequelae. Recent studies have raised hopes for innovative alternative treatment strategies for mucormycosis (Armstrong‐James et al , ; Castillo et al , ) Currently, surgical debridement is strongly recommended for rhinocerebral and soft‐tissue mucormycosis according to the ECIL‐6 guidelines and it is advised for case‐by‐case consideration for pulmonary and disseminated mucormycosis (Tissot et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…84 Treating T- inactivated cells with IL-2, IL-7, or both cytokines enhances the production of Mucorales-specific T cells and their cytokines IL-5, IL-10, IL-13, and also stimulates the production of CD4+ T cells that are a specific Mucorales antigens. 85 This new immune therapeutic method is a promising way to increase the response of T cells against mucormycosis. 85…”
Section: Interaction Of the Mucorales With The Immune Systemmentioning
confidence: 99%
“…Moreover, in the patients with hematological malignancies, T cells produced a characteristic cytokine profile with IL-10 secreted during the initial stages of the infection, followed by IFN-γ and IL-4 production at later time points [ 38 ]. On the contrary, another study showed that T cells from healthy donors have a low reactivity to R. oryzae and low IFN-γ production [ 37 ]. These discrepancies may rely on the methods used for the evaluation of specific-T cell activity.…”
Section: Production Of Cytokines By T Cells In Response To Mucoramentioning
confidence: 99%
“…Recently, Castillo et al found that the treatment of T cells with a combination of IL-2/IL-7 induce a proper expansion of R. oryzae -specific T cells with a strong production of IL-13, IL-5, TNFα, and IL-10. Therefore, the authors considered the expansion of rare Mucorales-specific T cells from healthy donors to be used for potential adoptive immunotherapy [ 37 ]. Page et al evaluated Mucorales-specific T cells and cytokine profiles in healthy donors as biomarkers of environmental mold exposure.…”
Section: Production Of Cytokines By T Cells In Response To Mucoramentioning
confidence: 99%
See 1 more Smart Citation